Navigating the complexity of exposure to multiclass organic pollutants in respirable size-resolved particles and implications for oxidative potential - Zhang, Ying-Jie; Xu, Ting-Ting; Luan, Yu-Ling; Shen, Hui-Min; Guo, Ying (Environment international, 2025)
[Display omitted] •Pollutants in 9–10 µm fractions markedly enhance the formation of oxidation.•Benzo[g,h,i]perylene was the primary contributor to oxidation among mixtures.•Particle size and components are key drivers influencing oxidative potential.•Elevated mass concentrations do not necessarily indicate severe oxidative toxicity. Chronic exposure to inhalable atmospheric particulate matter is linked to millions of annual premature deaths globally. Yet the sources and factors driving oxidative potential (OP) remain poorly understood, especially regarding the coexistence of multi-organic pollutants. This longitudinal study examined the size-distribution, respiratory deposition efficiency and daily exposure of 41 chemicals covering polycyclic aromatic hydrocarbons (PAHs), brominated flame retardants (BFRs), and phthalates (PAEs), as well as the dithiothreitol-based OP in size-fractioned PM10 from distinct waste recycling plants in Guangzhou, South China. From September to December 2020, five parallel samples were successively collected within each of the four plants using an eight-stage cascade sampler. The particle size-dependent correlations were explored between co-existing pollutants and acellular OP, with a weighted quantile sum regression model to rank the relative contribution ratios. The ∑8PAE levels in PM10 were 100 and 1000 times higher than those of ∑16PAH and ∑17BFR respectively, aligning with the exposure outcomes of dermal contact and inhalation pathways. Compounds in the coarse fractions of PM9.0–10 primarily deposited in the upper respiratory tract, while 37%–73% in pulmonary alveoli were attributed to finer PM2.1. The high-molecular-weight PAHs and BFRs in PM9.0–10 were more effective in enhancing OP generation than PAEs, with benzo[g,h,i]perylene identified as the most potent oxidizing agent with the highest weight (22%). The findings underscore that elevated pollution burden doses may not necessarily represent severe oxidative toxicity, and the targeted prevention strategies are warranted to mitigate oxidative toxicity from respirable particle.